Map, detect and research Botryosphaeriaceae species - Batista, Eduardo Vaz Lemos Pires (2022)
The family Botryosphaeriaceae (Botryosphaeriales, Ascomycetes) is known to include several species of opportunistic pathogens or latent endophytes that affect worldwide many angiosperm and gymnosperm hosts. These fungi usually attack plants exposed to environmental stress, like drought or plants that are already affected by other pathogens or pests. Diseases caused by these species result on fruit rots, leaf spots, seedlings damping-off and collar rot, cankers, blight of shoots and seedlings and eventually host death. The number of studies targeting the distribution, diversity, ecology, and pathogenicity of Botryosphaeriaceae species is consistently increasing. However, with the lack of consistency in species delimitation, the name of hosts, and the locations of studies, it is almost impossible to quantify the presence of these species worldwide, or the number of different hosts–fungus interactions that occur. Also, several questions regarding pathogenicity potential and the capability of these organisms to jump among different hosts in a global change scenario is poorly understood. The present thesis offers in chapter two, a broad perspective on Botryosphaeriaceae species global diversity, dispersion, host association, ecological niches, pathogenicity and communication efficiency of new occurrences and new host-fungus associations based on a worldwide cured dataset. This dataset, with more than 2900 literature references from 1692 different plant species in 149 countries was transformed in an interactive and open database that allows the end-user to easily consult and explore information. In chapter three, reflects and assess best practices for new fungal species descriptions to ensure reproducibility, transparency, and consistency over time. Based on our definition of best available practices, it was found that, from a representative group of 210 new fungal descriptions, over 90% of the descriptions are followed by a detailed morphological characterization and with consistent phylogenetic analyses, for molecular characterization and host-fungus interactions 60% of the descriptions are outdated or only meet the minimal requirements for publication and 50% of the authors do not provide enough accessible and reproducible information. Chapter four evaluates how these species may shift their ecological ranges in response to current and future climate changes. An overall increase of suitable areas for these pathogens was predicted in most of the future scenarios and a consistent increase of the optimal growth months, for fungi development, that eventually could impact the phenology of these organisms and originate more frequent and intensive outbreaks. Additionally, in chapter five, as a case study, a survey was conducted in Portugal to identify Botryosphaeriaceae species associated with the main forest tree species. Twelve different species were identified, and pathogenicity tests revealed the host-jump potential of some species, showing high susceptibility of Quercus suber to Neofusicoccum parvum and N. eucalyptorum and of Pinus pinaster to Diplodia corticola. Different perspectives were explored to contribute for a better understanding of the challenge that Botryosphaeriaceae-related diseases represent in a global change scenario.